Bioaccumulation of heavy metals, Ni, Cd and Pb in muscle, liver and caviar of farmed Acipenser baerii from Khuozestan Province - A Mohammad Salehi; Velayatzadeh Velayatzadeh; N Karami Rad (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2017)
The presence of heavy metals in our environment has been of great concern because of their toxicity when their concentration is more than the permissible level. These metals enter in the environment by different ways e.g. industrial activities. This study was carried out to determine and comparison of heavy metals Cd, Pb and Ni in muscle, liver and caviar of farmed Acipenser baerii from Khuozestan Province, 2014. 30 samples of Acipenser baerii were prepared randomly from five ponds of Hantoshzadeh breeding. Heavy metal levels in fish samples were analyzed by Perkin Elmer 4100 zl atomic absorption. Data analysis was performed with the software SPSS17 and comparison of the mean to T-test. The highest concentration of Ni, Cd and Pb were 1.10±0.23, 0.041±0.002 and 0.35±0.02 µ/Kg in liver of Acipenser baerii. The lowest concentration of this metals were obtained 0.08±0.003, 0.017±0.002 and 0.11±0.02 µ/Kg in caviar this species. Concentration of heavy metals in the liver of Acipenser baerii was higher than muscle and caviar. In this study concentration of Ni, Cd and Pb in muscle and caviar of Acipenser baerii were lower than comparison of WHO, FDA, MAFF and NHMRC standards.